2015
DOI: 10.4171/ggd/333
|View full text |Cite
|
Sign up to set email alerts
|

A Thompson group for the basilica

Abstract: Abstract. We describe a Thompson-like group of homeomorphisms of the Basilica Julia set. Each element of this group acts as a piecewise-linear homeomorphism of the unit circle that preserves the invariant lamination for the Basilica. We develop an analogue of tree pair diagrams for this group which we call arc pair diagrams, and we use these diagrams to prove that the group is finitely generated. We also prove that the group is virtually simple.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…J. Belk and B. Forrest [BF15a] introduced the Basilica Thompson group T B (defined in Definition 1.10 below). They showed that it is virtually simple, generated by four elements, and is a sub-as well as a supergroup of Thompson's group T .…”
Section: Introductionmentioning
confidence: 99%
“…J. Belk and B. Forrest [BF15a] introduced the Basilica Thompson group T B (defined in Definition 1.10 below). They showed that it is virtually simple, generated by four elements, and is a sub-as well as a supergroup of Thompson's group T .…”
Section: Introductionmentioning
confidence: 99%
“…This group is also a special case of a rearrangement group, where the basilica is realized as a limit space of a sequence of graphs in an appropriate way. We conjectured in [1] that T B is not finitely presented, and this was recently proven by S. Witzel and M. Zaremsky using the CATp0q complex we describe here [19].…”
Section: Introductionmentioning
confidence: 52%
“…The rearrangement group T B for the basilica replacement system from Example 1.5 is called the basilica Thompson group. In [1] the authors proved the following facts about this group:…”
Section: Examplesmentioning
confidence: 94%
See 2 more Smart Citations